Direct Evaporative Cooling System for Year-Round Thermal Management with Solar Assisted Dryer: An Experimental Investigation - Sujatha Abaranji; Karthik Panchabikesan; Velraj Ramalingam (Novel Perspectives of Engineering Research Vol. 10, 2022)
The extensive use of air conditioners achieves building cooling. Thermal comfort is provided by mechanically powered devices that degrade the environment through increasing energy usage. Building cooling systems that are both energy-efficient and environmentally friendly are becoming increasingly important as a means of reducing environmental degradation. Evaporative cooling, a common passive cooling method, might meet energy demand while also addressing global climate challenges. The sensible cooling of air is achieved in traditional direct evaporative cooling by continuous water circulation over the cooling pad. Despite its ease of use, the pad material issue and water stagnation in the sump limit its application. Furthermore, the constant functioning of the pump increases the amount of electrical energy consumed. The objective of the present work is to eliminate the pump and sump using a porous material that acts as the water storage medium. Experiments are conducted to study the performance of the vermicompost based evaporative cooling system for three different RH conditions (low, medium, and high) at Vellore, India, a place with hot-dry weather conditions. The performance of a direct evaporative cooling system is evaluated by determining its cooling capacity, effectiveness, and water evaporation rate. Because of its high water retention properties, vermicompost is used to replace the pump and sump. There is no need to switch materials every time. However, at the end of the trial, the vermicompost is regenerated using a solar dryer. The passage of heated air over the vermicompost also prevents the transfer of any mould spores present in the air. During low RH conditions, vermicompost produces an average temperature drop of 9.5°C, according to the findings. Furthermore, by eliminating the pump, vermicompost contributes to a 21.7 percent energy reduction. As a result, vermicompost could be a more energy-efficient alternative to the traditional evaporative cooling system’s pad-pump-sump. Further, integrating a solar-assisted dryer with the direct evaporative cooling system can provide a clean and sustainable indoor environment. This system could pave the way for year-round thermal management of building cooling applications with environmental safety.